RENEWABLE ENERGY POTENTIAL IN PAKISTAN AND BARRIERS TO ITS DEVELOPMENT FOR OVERCOMING POWER CRISIS - HABIB, SHEEBA; IQBAL, KANWAR MUHAMMAD JAVED; AMIR, SARAH; NASEER, HAFIZ MUHAMMAD; AKHTAR, NADIA; REHMAN, WAJIH UR; KHAN, MUHAMMAD IRFAN (The journal of contemporary issues in business and government, 2021)
This paper has critically analyzed barriers to development of potential renewable energy resources to resolve the power crisis in Pakistan. The study was limited to the electric power sector and based on secondary data, experts’ opinions and stakeholder consultations. The study tried to explore the question: why the available substantial renewable energy sources in the country are not being tapped to produce electricity and what are the barriers in development of the power sector of Pakistan? Energy experts and stakeholders including government officials and environmental experts were consulted. Focused group discussions and individual consultations were made for seeking opinions and ideas about development and promotion of renewable energy for the power sector. The findings of the study showed that Pakistan’s total installed power generation capacity is 39000 MW and the contribution of renewable energy is less than 10% (6% from renewable: wind, solar and bagasse) as compared to conventional sources of energy despite its huge potential. There are political as well as technical, financial and social issues which marginalize renewable energy in the country. In order to improve the situation, there is a dire need to prioritize options in the energy sector and to promote renewable energy by providing strong financial, technical and legal support. Moreover, political stability, visionary leadership and pragmatic and integrated power policy/energy plan are required to promote renewable energy exploitation in the country. It is hoped that this study will help to pinpoint the loopholes and gaps in the development of the power sector along with factors hindering the development and promotion of renewable energy in Pakistan. Based on the findings, it is suggested that improved governance with strategic planning and appropriate implementation mechanisms in the power